Screening of castor hybrids and their parents against wilt disease: SCREENING OF CASTOR HYBRIDS AND THEIR PARENTS AGAINST WILT DISEASE - DIYOL ASHA; P T PATEL; A M PATEL; Y N PATEL (Journal of Oilseeds Research, 2024)
Castor is an industrially important non-edible oilseed crop widely cultivated in the arid and semi-arid regions of the world. Wilt (Fusarium oxysporum f. sp. ricini) disease has become a serious problem in India, though wilt resistant hybrids viz., GCH-4, GCH-5, GCH-7, GCH-8, GCH-9 and GCH 10 have been released. So investigation on screening of castor hybrids and their parents against wilt disease was undertaken under poly house conditions. The results revealed that out of six, three parent's viz., SKP-84, JI-368 and 48-1 were resistant, while two hybrids i.e. SKP-84 x JI- 368 and GEETA x SH-72 were found resistant to wilt disease. Parent GEETA found moderately resistant, whereas susceptibility for the disease was observed in parents viz., VP-1, VI-9, SH-72 and JI-35 and Hybrid VP-1 x VI-9 reported susceptibility to wilt disease. Our findings confirmed the importance of selecting the parents for the development of resistant hybrids in disease-resistance breeding programmes.